2011
DOI: 10.1007/s00125-011-2183-8
|View full text |Cite|
|
Sign up to set email alerts
|

mRNA of the pro-apoptotic gene BBC3 serves as a molecular marker for TNF-α-induced islet damage in humans

Abstract: Aims/hypothesis TNF-α plays important roles in the pathogenesis of type 1 and type 2 diabetes mellitus. In light of this, we examined the involvement of a pro-apoptotic gene, BBC3 (also known as PUMA), in TNF-α-mediated beta cell dysfunction and destruction in human islets. Methods Human islets were exposed in vitro to TNF-α alone or in combination with IFN-γ. Gene expression was assessed by RT-PCR using a set of single islets. Protein abundance and cellular localisation of BBC3 were assessed by immunoblot and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…Similar to our findings, it has recently been demonstrated that pro-inflammatory cytokines including TNF α can induce Puma expression via an NF- κ B-mediated pathway in colorectal cancer cells and islet β -cells. 46, 47, 48 NF- κ B has been reported to promote survival or cell death depending on the context. 27, 28 The protective effects of NF- κ B have been attributed to its ability to induce the expression of anti-apoptotic factors such as Bcl-2, Bcl-X L , and cIAP2.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, it has recently been demonstrated that pro-inflammatory cytokines including TNF α can induce Puma expression via an NF- κ B-mediated pathway in colorectal cancer cells and islet β -cells. 46, 47, 48 NF- κ B has been reported to promote survival or cell death depending on the context. 27, 28 The protective effects of NF- κ B have been attributed to its ability to induce the expression of anti-apoptotic factors such as Bcl-2, Bcl-X L , and cIAP2.…”
Section: Discussionmentioning
confidence: 99%
“…Він визнаний одним із головних цитокінів, які індукують апоптоз інсулінпродукувальних клітин шляхом впливу на проапоптичний ген BBC3 (РИМА), і таким чином відіграє суттєву роль у патогенезі ЦД [5,19,21].…”
Section: вступunclassified
“…Three days prior to transfection, INS-1 cells were cultured in a 24-well plate (Corning Life Sciences, Tewksbury, MA) (70 ϫ 10 3 cells/well) with INS-1 culture media not containing antibiotic-antimycotic. INS-1 cells and islets isolated from the pancreata of Firefly rats were transfected with 50 nM of Bbc3 siRNA or 50 nM of a nontargeting scrambled control siRNA (SMARTpool siRNA, GE Dharmacon), using the DharmaFECT transfection reagent (GE Dharmacon) as described previously (31). The transfection rate was confirmed to be Ͼ80% in the INS-1 cells and Ͼ25% in the islets.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown previously that BBC3 expression is upregulated in human islets after exposure to recombinant human TNF␣ or in combination with IFN␥, leading to ␤-cell apoptosis through the mitochondrial pathway in vitro (31). High BBC3 mRNA levels in human islets are associated with poor graft function after transplantation in streptozotocin-induced diabetic NOD Scid mice.…”
mentioning
confidence: 99%